Levels of Mind Habits for Post-Graduate Students in View of the Variable Gender and Academic Level - Alakashee, Bushra (Dirasat: Educational Sciences, 2021)
This study aims to identify the level of habits of mind (striving for accuracy, thinking interdependently, questioning and posing problems) of graduate students at the University of Sharjah. The study sample consisted of (100) masters and doctoral students selected in a stratified random method, enrolled in the Faculty of Arts and Sciences in the academic year 2018-2019. Students responded to a questionnaire prepared by the researcher according to the Costa and Kallick classification. The results of the study indicated that the level of the habits of mind among the sample members is high, and the results of the (T) test for independent groups indicated that there were no statistically significant differences at (α = 0.05) in striving for accuracy, and thinking interdependently, according to gender, and that the statistical difference was in questioning and posing problems in favor of males. Further, there was no statistically significant difference at (α = 0.05)) in thinking interdependently according to students’ study level (master’s/doctoral), while the differences were statistically significant in striving for accuracy, and question and posing problems, in favor of master’s and doctoral students, respectively. In light of the study results, the researcher recommends to utilize modern teaching methods and curriculum, and to organize workshops and training programs that focus on developing the habits of mind for university students.